Pengelolaan dan penggunaan dana desa pada Kecamatan Babussalam Kabupaten Aceh Tenggara Provinsi Aceh tahun 2019-2021 - Malahayati, Rina; Isnaini, Isnaini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research is to find out whether the use of village funds reduces village poverty rates, encourages village economic growth, reduces village unemployment rates, reduces village school dropout rates, and whether village fund management is guided by the principles of transparency, accountability, and participation. This research was conducted using a survey-based quantitative approach. measurement using a Likert scale. The population of this study came from 27 villages located in Babussalam District, Southeast Aceh, and Aceh. Using SPSS software, validity tests, reliability tests, multiple linear regression tests, coefficient of determination tests, t tests, and F-tests were carried out in analyzing the data. The study's findings are as follows: transparency, accountability, and participatory simultaneous and partial effects on the management of village funds, as well as the use of village funds for the poor, which are always budgeted for in 2019-2021; economic growth is evenly distributed; village unemployment can be handled by each village's efforts to provide assistance for the development and development of productive economic enterprises; and to reduce the dropout rate in villages by sending village children to continue their education at Gunung Leuser University from 2018-2021 in each village.